Fun Mathematics Learning Design with an Inquiry Learning Approach to Improve Student Learning Outcomes - Rajak, Faysal; Wahyuningsih, Wahyuningsih; Prasetyo, Erwin (Lembaga Riset Mutiara Akbar, 2023)
This study aims to determine the design of a fun mathematics learning with an inquiry learning approach to improve student learning outcomes. This research was conducted at MTs Muhammadiyah Al-Fatah Nangahale in the second semester of the 2021-2022 academic year. The population of this study amounted to 20 students who were all studied. This research uses classroom action research method. Data collection techniques using tests and documentation. The results showed that the design of learning mathematics can please students by using an inquiry learning approach to increase student learning outcomes. In the data analysis, it shows that the first cycle of student learning outcomes with an average of 74.5 with a percentage of 80% while the second cycle of student learning outcomes with an average of 78.34 with a percentage of 85% so that from the average learning outcomes and large percentage of participants students have increased